Intelligence theory from the margins: questions ignored and debates not had. Issue 4 (7th June 2018) - Bean, Hamilton
Abstract: This article explores post-2009 contributions to intelligence theorizing that focus on critique and transformation of dominant IS ontologies and epistemologies. This exploration illuminates diverse theoretical resources that can help reveal hidden or misunderstood intelligence-related phenomena. The article contributes to recent calls for establishing a Critical Intelligence Studies subfield that attempts to move associated scholarship from the margins of Intelligence Studies to a more visible and influential position within the field.